Community Perceptions and Preferences Toward Tourism Village Development in Kojadoi Village, East Alok Subdistrict, Sikka Regency, East Nusa Tenggara Province - Wardana, Hananu Wisnu; Muthmainnah , Muthmainnah; Molo, Hasanuddin; Ariandi, Rahmat (Forestry Department, University of Muhammadiyah Makassar, 2023)
The purpose of this study was to determine the Perceptions and Preferences of the Community towards the Development of Tourism Villages in Kojadoi Village. This research was conducted with descriptive analysis with a percentage analysis approach. Sample determination was carried out using the Slovin formula. The population in this study is the entire community, namely 486 heads of families (KK) and visitors who visit Kojadai Tourism Village, namely 1,184 people. The total number of respondents was 82 local people and 93 visitors, sample details were carried out on visitors, and local people (including Pokdarwis, BUMDES, and community leaders). This research uses a Likert scale, where the Likert scale is used to measure the attitudes, opinions, and perceptions of a person or group of people about social phenomena. The data analysis process begins by reviewing all data obtained both through the results of questionnaires and interviews, then described by using percentage analysis. The results showed that community perceptions of tourism village development were considered quite good with an average scale of 4.08 and tourist preferences for the development of Kojadai tourism village were classified as very good, with a preference level on an average scale of 4.24.